Removal of Petroleum Products from Water Surface by Chemically Modified Wood Waste - Yakovlevna Sippel, Irina; Albertovna Akhmetgaleeva, Gulnaz (International Journal of Psychosocial Rehabilitation, 2019)
In this work, they studied the possibility of woodwork waste use to remove oil products from the water surface by the sorption method. We used sawdust of ash (Fráxinus excélsior) and linden (Tília cordáta) as sorption materials, formed at the woodworking enterprises of the Republic of Tatarstan, as sorbates - fresh and used diesel engine oils, characterized by high boiling points and heavy fractional composition. To increase the sorption capacity of wood waste, they were chemically modified with the solutions of sulfuric, nitric, hydrochloric, perchloric, phosphoric and acetic acids with the concentration of 0.5, 1 and 3%. They determined the values of the maximum oil absorption of the initial and modified samples of sorption materials in relation to fresh and used motor oils. It was established that ash and linden sawdust modified with a 3% solution of nitric acid have the highest sorption properties. Determination of the sorption capacity by iodine and methylene blue showed that modified sawdust, in comparison with the initial samples, has a more highly developed surface, combining different types of pores: both micro- and mesopores. Experiments on modeling engine oil spills on water surface showed that chemically modified sawdust are effective sorbents of oil products, the degree of water purification reaches 99%